An activity-based costing model for stategic decisions in transportation on demand projects - Oliveira, Joaquim Vítor (2011)
Today there are many people who lack access to adequate means of transportation (people with reduced mobility, elderly, people in rural areas of low population density, etc.). In these cases the conventional solutions do not serve and tend to worsen due to increased costs of private transport and the reduction of conventional transmission lines at these sites. In this context, emerged alternative transportation models called "transportation on demand". However, although there are some experiments, these new models are still not consolidated due to problems of technical and conomic. Beyond the technical aspects necessary to develop cost models suitable for designing a system with economic viability and to set prices and pricing policies that ensure the attractiveness of the service without compromising their economic viability (namely with recipe above cost). The complexity of this system and the relative weight of significant indirect costs justify the application of a costing system based on activities. In this article we present a cost analysis based on the strategic ABCM model to discuss the conditions of economic viability of a transport on demand system applied to the municipality of Terras de Bouro. These results are important to support strategic and operational decisions.